Enhancing Knowledge Sharing on Social Media: The Role of Functionalities in User Engagement and Information Quality - Natalia Kristian; Dana Indra Sensuse; Sofian Lusa (Jurnal Indonesia Sosial Teknologi, 2024)
This study investigates functionalities on social media platforms that promote effective knowledge sharing, focusing on information quality and user engagement. A systematic literature review (SLR) was conducted to analyze relevant research. The findings reveal that functionalities like content creation and curation tools, user interaction and feedback mechanisms, community building and gamification elements, and knowledge filtering and recommendation systems all contribute to a positive knowledge-sharing environment. These functionalities empower users to create high-quality content, engage in discussions that refine information, and discover trustworthy sources. The study highlights the potential of social media platforms for knowledge sharing but acknowledges that the effectiveness of functionalities can vary depending on the platform and audience. Future research is recommended to explore the most impactful functionalities in specific contexts and the interplay between functionalities, user behavior, and information quality.